Left atrial function, inflammation, and prothrombotic response after radiofrequency ablation for atrial fibrillation. Issue 5 (May 2018) - Yin, Guangli; Xie, Ruiqin; You, Ling; Yin, Hongning; Sun, Yucui; Wu, Jinglan; Zhao, Yansha; Geng, Xue; Zhang, Yanan
Abstract : Background: : The conversion of atrial fibrillation (AF) to sinus rhythm is associated with transient dysfunction of the left atrium (LA). This study aimed to investigate the time course of LA function and inflammation after radiofrequency (RF) ablation for paroxysmal AF. Methods: : Fifty‐three patients with paroxysmal AF undergoing RF ablation were recruited. White blood cells were counted and high‐sensitivity C‐reactive protein (hs‐CRP), fibrinogen, and D‐dimer levels were measured. LA emptying fraction, strain, and strain rate were evaluated before RF ablation and at 1, 2, 3, and 4 weeks and 2 and 3 months after ablation using conventional Doppler echocardiography and two‐dimensional speckle‐tracking echocardiography. Results: : LA emptying fraction sharply decreased at day 7 after ablation and then slowly increased ( p < 0.05) and returned to the baseline value at day 28. LA strain and strain rate values sharply decreased at day 7 after the procedure and then slowly increased ( p < 0.05). A significant correlation between hs‐CRP level and LA emptying fraction was found at day 7. Conclusion: : Reduced LA function and increased prothrombotic tendency were found at ˜1 week after AF ablation for paroxysmal AF. Therefore, monitoring the time and degree of anticoagulation after ablation for paroxysmal AF might effectively prevent thromboembolic events and reduce anticoagulant cost and bleeding risk.